"An Evaluation of the Changes in the Free Gingiva after Orthodontic Movement of the Upper Ectopic Canines" (Journal of Hama University, 2022)
Investigating the movement of free gingiva during orthodontic alignment of upper ectopic canine, using tattooing mark points on the free gingiva.In this study, 13 patients (7 males, 6 females) with malocclusion (Upper ectopic canine) were treated. The upper first premolars were extracted, after two weeks of the extraction, tattooing marked points were placed on the free gingiva, and the measurements were taken using digital Vernier caliper. Closed I loops made of Stainless steel were used to retract the upper canines.The results of this study showed significant differences between the movement of the free gingiva and the movement of corresponding upper canines (P